"Should I tell?": moral reflexivity in 14 whistleblower autobiographies - Olesen, Thomas (Journal of business ethics, 2025)
Who is the whistleblower, and how do they reach the difficult decision to blow the whistle? The article argues that the extant literature has not paid sufficient attention to the profound moral reflexivity in this transition from employee to whistleblower. What is missing, in particular, is a better, sociologically informed, understanding of the various social domains in which whistleblowers are embedded. These domains are important because they provide different kinds of resources for the whistleblower’s moral reflexivity. To pursue this idea, the article conducts a qualitative analysis of 14 whistleblower autobiographies. The analysis is structured around four social domains, which are prevalent in the material: Childhood and adolescence, professional ethics, organizational loyalty, and societal and civic duty values. The autobiographical data clearly demonstrate how whistleblowers actively draw on these domains, and often several of them, as they justify and give meaning to their actions. Such a multidimensional understanding of the whistleblower’s social embeddedness opens up to new ways of analysing the deep personal and moral challenges that most whistleblowers experience.